História das pessoas comuns: uma influência temático-conceitual nas pesquisas do núcleo de história e memória da educação da Universidade Federal do Ceará - Costa, Francisco Joel Magalhães da (2021)
The objective of this study is to understand the relationship between History, the “common people” and the dissertations and theses produced between the Years 2000 to 2018, by the Center for History and Memory of Education (NHIME), of the Graduate Program in Education (PPGE), Faculty of Education (FACED), Federal University of Ceará (UFC). The central question of the research concerns the research of the “common people”, who are, from the historical point of view, those forgotten or ignored by Traditional History, in the name of kings, nobles, powerful, political and military. Common people include women, children, the elderly, the disabled, delinquents, blacks, the poor, homosexuals, insane people, among others. Thus, the study highlights the historical investigations about experiences, knowledge, social, cultural and educational practices, rescue and insertion of the “common people” in History. The research approach is of a qualitative nature, whose tipology is exploratorybibliographic, which adopted the Historical Method for the construction of this thesis. The techniques of information collection and data generation used literature review of secondary sources and digital sources, whose technical procedures of organization and analysis used were the State of the Art and Discourse Analysis. The theoretical foundation was anchored in the concepts of Escola dos Annales, History of ordinary people, History of Education, History seen from below, History of women, among others. The results showed 52 surveys that investigated the history of children, people with disabilities, delinquents, marketers, graffiti artists, the elderly, immigrants, fishermen, young people, graffiti artists, fanzineiros, teachers, women and blacks. This result corresponds to 52 (48%) works, in a total of 109 produced by NHIME, divided into 36 dissertations and 16 theses. It was concluded that the studies on the “common people” are evidenced from the theories of History, mainly with the French historiography, through the Annales, and the English historiography, through the English Marxists; that the theoretical and methodological resources that outline research on “ordinary people” are involved with the elements of oral tradition; and that all classes have knowledge that they add to our Society.